2022
DOI: 10.14740/gr1498
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use in Patients With Chronic Liver Disease and Cirrhosis: Current Evidence and Future Directions

Abstract: Chronic liver disease (CLD) and its complications constitute a significant cause of mortality and morbidity worldwide. Most deaths are secondary to the decompensation of cirrhosis and evolution of portal hypertension (PHTN). Since disease progression reversal is hardly attainable after decompensated cirrhosis develops, it is essential to intervene early with a therapeutic agent or regimen that could prevent or slow disease evolution. Thus far, there has been no agreed-upon medication to help in the fight again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…However, patients receiving statins had numerically longer median OS (17.2 months) compared to patients not receiving statins (13.4 months). Even though we cannot ascertain that statins were prescribed before lenvatinib treatment, and we could not directly link statins with development of CSTE‐HTN or improved OS, previous studies have indicated survival benefits from statins in advanced liver disease 23,42,43 . In contrast, β‐blockers (that could have been administered at enrollment or during lenvatinib treatment due to treatment‐emergent HTN) showed no benefit in increasing OS.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, patients receiving statins had numerically longer median OS (17.2 months) compared to patients not receiving statins (13.4 months). Even though we cannot ascertain that statins were prescribed before lenvatinib treatment, and we could not directly link statins with development of CSTE‐HTN or improved OS, previous studies have indicated survival benefits from statins in advanced liver disease 23,42,43 . In contrast, β‐blockers (that could have been administered at enrollment or during lenvatinib treatment due to treatment‐emergent HTN) showed no benefit in increasing OS.…”
Section: Discussionmentioning
confidence: 82%
“…11 In our post hoc analysis, CSTE-HTN occurred in 44.5% of patients receiving lenvatinib, a percentage comparable to the prevalence of HTN in the general population adjusted by age (45.4%), 37 the incidence of HTN associated with angiogenic agents (19%-67%), 38 and the prevalence of HTN as a cardiovascular comorbidity in cancer registries (38%). 23,42,43 In contrast, βblockers (that could have been administered at enrollment or during lenvatinib treatment due to treatment-emergent HTN) showed no benefit in increasing OS. In-depth studies are, however, needed to validate this preliminary exploratory data.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sodium-glucose transporter inhibitors (SGLT-2i) may have a role in the treatment of MASH by reducing liver stiffness measurement, although not confirmed yet by high-quality RCTs if this is a direct liver effect or from controlling metabolic and cardiorenal disturbances [28]. Growing evidence from emerging retrospective studies and RCTs demonstrates a potential benefit of atorvastatin use in patients with chronic liver disease by improving the clinical outcomes and liver histology and enzymes, but additional large prospective RCTs are needed to be conducted to further explore the association between statin exposure and the risk of liver disease progression [29]. In the same context with other medical treatments, although metformin had demonstrated promising results in experimental studies on the reversal of cirrhosisrelated histologic changes, these findings were not confirmed in subsequent clinical trials [27].…”
Section: Discussionmentioning
confidence: 99%
“…Stable cholesterol levels, despite the increased use of statins, is coherent with previous data showing increased cholesterol levels after HCV eradication [ 22 , 26 , 27 ]. The effect of statin on fibrosis levels is yet to be clarified; however, some studies showed an association of the former with decreased inflammation and fibrosis [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%